(untitled) (Boston, 2005)
Introduction to Computer Security is adapted from Bishop's comprehensive and widely praised book, Computer Security: Art and Science. This shorter version of the original work omits much mathematical formalism, making it more accessible for professionals and students who have a less formal mathematical background, or for readers with a more practical than theoretical interest
An toàn hệ thống
Keywords: Bảo mật máy tính,Computer security